2021
DOI: 10.1001/jamaoncol.2021.3701
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Pancreatic Cancer Among Individuals With Pathogenic Variants in the ATM Gene

Abstract: IMPORTANCE Pathogenic germline variants in the ATM gene have been associated with pancreatic cancer risk. Although genetic testing identifies these variants in approximately 1% to 3% of unselected patients with pancreatic cancer, the lifetime risk of pancreatic cancer among individuals with pathogenic ATM variants has not been well estimated.OBJECTIVE To estimate age-specific penetrance of pancreatic cancer in individuals with a pathogenic variant in the ATM gene. DESIGN, SETTING, AND PARTICIPANTSThis was a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Low risk was seen for CHEK2 (both cohorts). The high risk of PDAC in ATM heterozygotes has been described before in a multicenter cohort [28]. Interestingly, this finding contrasts with the more moderate risk that has been estimated for breast cancer in this gene [29].…”
Section: Discussionmentioning
confidence: 56%
“…Low risk was seen for CHEK2 (both cohorts). The high risk of PDAC in ATM heterozygotes has been described before in a multicenter cohort [28]. Interestingly, this finding contrasts with the more moderate risk that has been estimated for breast cancer in this gene [29].…”
Section: Discussionmentioning
confidence: 56%
“…Variants in BRCA and ATM genes occur in both hereditary and sporadic PDAC causing deficiency in DNA repair pathways and provoke genomic instability (Perkhofer et al., 2021). In a recent study of 130 families with 2,227 family members with FPC predisposition, it was shown that individuals with an ATM variant had a cumulative risk for pancreatic cancer of 6.3% by age 70 and 9.5% by age 80 (Hsu et al., 2021). Both ATM and BRCA2 variants have previously been identified as inherited germline variants related to pancreatic cancer (Hu et al., 2018; Huang et al., 2018; Zhen et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ataxia telangiectasia is a complex autosomal recessive syndrome caused by germline mutations in the ATM gene, which increase sensitivity of cells to potentially mutagenic environmental factors (e.g., sunlight) and susceptibility to malignant transformation. The disease is known for neurological manifestations and vascular anomalies, but the ATM variant carriers also have a 6.5-fold risk of PDAC [ 42 ].…”
Section: Genetic Susceptibility Syndromesmentioning
confidence: 99%